Shifting landscapes: dynamic changes from pro- to anti-inflammatory leukocyte phenotype in myocardial ischemia/reperfusion injury - Kröning, Pia; Mauler, Maximilian; Schanze, Nancy; Naber, Katharina; Stallmann, Daniela; Dürschmied, Daniel; Westermann, Dirk; Gauchel, Nadine (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe temporal and spatial dynamics of platelet-leukocyte complex (PLC) formation in myocardial ischemia reperfusion injury (I/R injury) are still ill defined.AimTo investigate the kinetics and spatial differences of platelet-monocyte (PMC) and platelet-neutrophil (PNC) complex formation over the first 7 days in a mouse model of myocardial I/R injury.MethodsA time-course study was conducted up to 7 days in order to evaluate immune cell response and cardiac function following myocardial I/R injury in mice. Myocardial I/R injury was induced by ligation of the left anterior descending coronary artery (LAD) for 30 min followed by reperfusion. Using flow cytometry leukocyte and platelet markers were evaluated in the heart, blood, spleen, and bone marrow. Echocardiography was performed in order to measure ejection fraction and fractional shortening which are accepted indicators of cardiac function.ResultsExpression of CD206-Geometric Mean Fluorescence Intensity (GMFI) indicative of an anti-inflammatory phenotype in neutrophils (N2) increased in PNCs at day 7. A statitstically significant decrease in the percentage of anti-inflammatory Ly6Clow PMCs was observed as early as day 3, when compared to the baseline value. Flow cytometry analysis showed no significant variations in PNCs or PMCs within the area at risk (AAR) across the specified time points. A rise in neutrophils and monocytes was observed in the AAR, reaching its peak on day 3.ConclusionThe present study demonstrates that both anti-inflammatory Ly6Clow monocytes and N2 neutrophils participate in PLC formation following myocardial infarction (MI) and reperfusion. Our results suggest that the N2 phenotype prerequisite for PLC formation in AAR at day 7. These findings suggest that targeted interventions may be developed to improve outcomes after myocardial I/R injury.